Meningkatkan Kemampuan Koneksi Matematis Siswa Smp Melalui Model Pembelajaran Accelerated Learning Cycle (ALC) Dan Probing Prompting - Sahensolar, Jeklyn Aprilya; Susilowaty, Nora (LPPM Universitas Advent Indonesia, 2020)
Abstract. This research aimed to see how student’ mathematical connection ability, whether there are significant differences in improving students' mathematical connection ability, and how students respond to the Accelerated Learning Cycle (ALC) learning model and students who obtain the Probing Prompting learning model. This research used a comparative study design, which is a study that compares the ability of mathematical connections of two classes with different learning, namely the Accelerated Learning Cycle (ALC) learning model and Students who obtain the Probing Prompting learning model. This research involved two classes, they are 28 students from class VIII-E and 27 students from class VIII-A SMPN 2 Parongpong, Bandung Barat. The instrument used in this research are a description test of mathematical connections capability on the subject of the circle and student response questionnaire. The results showed that the improvement in mathematical connections capability who obtained the Accelerated Learning Cycle (ALC) learning model and the Probing Prompting model were relative hight. Based on the statistical tests, there was no significant difference between students who obtained the Accelerated Learning Cycle (ALC) learning model and Probing Prompting learning model. Students give responses that are